Optical and opto-acoustic imaging - Ntziachristos, Vasilis; Razansky, Daniel (Molecular Imaging in Oncology, 2013)
Since the inception of the microscope, optical imaging is serving the biological discovery for more than four centuries. With the recent emergence of methods appropriate for in vivo staining, such as bioluminescence, fluorescent molecular probes, and proteins, as well as nanoparticle-based targeted agents, significant attention has been shifted toward in vivo interrogations of different dynamic biological processes at the molecular level. This progress has been largely supported by the development of advanced optical tomographic imaging technologies suitable for obtaining volumetric visualization of biomarker distributions in small animals at a whole-body or whole-organ scale, an imaging frontier that is not accessible by the existing tissue-sectioning microscopic techniques due to intensive light scattering beyond the depth of a few hundred microns. Biomedical optoacoustics has also emerged in the recent decade as a powerful tool for high-resolution visualization of optical contrast, overcoming a variety of longstanding limitations imposed by light scattering in deep tissues. By detecting tiny sound vibrations, resulting from selective absorption of light at multiple wavelengths, multispectral optoacoustic tomography methods can now "hear color" in three dimensions, i.e., deliver volumetric spectrally enriched (color) images from deep living tissues at high spatial resolution and in real time. These new-found imaging abilities directly relate to preclinical screening applications in animal models and are foreseen to significantly impact clinical decision making as well © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-08